Concept of Distance Learning In University - Project Organization and Management - Vladimir Valentinovich Aleskovskiy; Tatiana Anatolievna Pavlova; Valery Vitalyevich Yanovskiy (Управленческое консультирование)
As a conceptual basis of distance learning we propose principles that are discussed. We put forward a E-learning method, based on them with the use of project management methodology. The use of project management methodology will contribute to the organization of an effective system of distance education. We proposed widely used the modern IT as a part of this methodology, including smart education, this will allow us almost completely automation of administrative work. The proposed technique of creative learning is almost ideally combined with principles and methods of total quality management (TQM), as we showed also. The suggested approach, we believe, will promote the growth the efficiency of the whole higher education system